2019
DOI: 10.1007/s00038-019-01297-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term civil conflict, migration, and the mental health of adults left behind in Thailand: a longitudinal study

Abstract: Objectives A long-term civil conflict has been occurring in the southernmost provinces of Thailand, and migration to Malaysia has been accelerated by this conflict. The objective of this work was to examine the influence of perceived effects of the unrest, migration of a household member, and children left behind on the reporting of psychiatric symptoms of working age adults. Methods A first round of data collection was conducted in 2014 including interviews with a probability sample of 1102 households and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although there is no evidence that the migrant population presents a higher prevalence of psychiatric diagnoses than the local population, there is evidence that gender can have an impact on the mental health of migrants and on the way in which symptomatology is linked to different experiences, depending on gender [ 78 ]. A review carried out in 2020 [ 79 ] found that studies focused on the mental health of migrants included gender as a variable, showing that among women, anxiety and the symptoms of depression were linked to having left behind children in their country of origin [ 80 ], receiving death threats and experiencing violence in their country of origin and during transit [ 81 ], and having experienced stress and anxiety while pregnant, during birth, and post-pregnancy [ 78 ]. Similarly, our study shows the consequences that migratory processes can have on the mental health of the women interviewed, and the need to design strategies for their protection and social integration in transit and arrival countries, as established by WHO guidance [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evidence that the migrant population presents a higher prevalence of psychiatric diagnoses than the local population, there is evidence that gender can have an impact on the mental health of migrants and on the way in which symptomatology is linked to different experiences, depending on gender [ 78 ]. A review carried out in 2020 [ 79 ] found that studies focused on the mental health of migrants included gender as a variable, showing that among women, anxiety and the symptoms of depression were linked to having left behind children in their country of origin [ 80 ], receiving death threats and experiencing violence in their country of origin and during transit [ 81 ], and having experienced stress and anxiety while pregnant, during birth, and post-pregnancy [ 78 ]. Similarly, our study shows the consequences that migratory processes can have on the mental health of the women interviewed, and the need to design strategies for their protection and social integration in transit and arrival countries, as established by WHO guidance [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Household and family stress is often reported in association with migration (Bhugra, 2004;Ford et al, 2019). Considering the quantitative data, more psychiatric symptoms were reported if there were children left behind.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to violent events has been found to increase traumatic stress disorder (PTSD) as well as depression and other mental health disorders (Ford et al, 2019;Jewkes et al, 2017;Miller and Rasmussen, 2010). Previous research has found an increased reporting of psychiatric symptoms associated with the unrest among working age Muslim adults in the southern provinces (Ford et al, 2017(Ford et al, , 2019. This study examines the presence of psychiatric symptoms among the migrants from this area to Malaysia.…”
Section: Study Setting-civil Conflict In Thailand's Southernmost Prov...mentioning
confidence: 93%
See 2 more Smart Citations